Safety Net Design and Systemic Risk: New Empirical Evidence - Ulrich Klüh (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
Recent econometric evidence has noticeably changed views on the desirability and the appropriate design of explicit Deposit Insurance Schemes (DIS). The purpose of this paper is to take a second look at the data. After surveying recent empirical work and providing a theoretical framework, we argue that existing studies may suffer from a selection bias. Building on a new database on explicit deposit insurance compiled by the author, we perform a variety of semi-parametric and parametric tests to see whether and how explicit deposit insurance (de)stabilizes banking systems. We find that the evidence indeed suggests that a selection bias is present. Controlling for this bias leads to a reassessment of recent studies. In particular, making deposit insurance explicit has a rather moderate and, if any, stabilizing effect on the probability of experiencing a systemic crisis.
urn:nbn:de:bvb:19-epub-662-8
Keywords: C14; G21; G28; 330; Deposit Insurance; Banking Fragility; Systemic Risk